Antecedents of buyer’s trust in marketing channels and an implementation in turkish valve market - İşçimen, Erkan (My University, 2007)
PAZARLAMA KANALLARINDA ALICI GÜVENİNİN BELİRLEYİCİLERİ VE TÜRK VANA PAZARINDA BİR UYGULAMA Hızlı değişen rekabet çevresi, işletmeleri rekabeti göğüslemek için daha yaratıcı ve esnek uygulamalara zorlamaktadır. Alıcı ve satıcı ilişkileri, yoğunlaşan rekabet ortamında giderek önem kazanmaktadır. Rekabet stratejisi olarak ilişkisel pazarlamada, dağıtım kanallarıyla başarılı ilişkiler oluşturma, sürdürme ve geliştirme yaklaşımıyla sadece dağıtım kanallarını değil şirketin tüm pazarlama faaliyetlerini kapsamaktadır. Uzun dönemli ilişkilerin yönetiminin artan önemi, araştırmacıları ve pazarlama profesyonellerini bu ilişkilerin belirleyicileri ve çıktıları konusunda çalışmaya itmiştir. Güven, alıcı ve satıcılar arasında uzun süreli ilişkilere erişmede anahtar etmen olarak ön plana çıkmaktadır. Bu çalışmada, Türk vana pazarında alıcı güveninin belirleyicileri açıklanmıştır. İletişim, tedarikçinin itibarı ve tedarikçinin finansal durumu pazarda alıcı güvenini etkileyen anahtar etmenler olarak görülmektedir.

ANTECEDENTS OF BUYER’S TRUST IN MARKETING CHANNELS AND AN IMPLEMENTATION IN TURKISH VALVE MARKET Rapidly changing competitive environment is forcing businesses to seek more creative and flexible means for meeting competition. Buyer – seller relationships is getting more importance day by day due to intensifying competition. Relationship marketing as a competitive strategy aims at creation, maintenance and development of successful relationships with marketing channels is currently considered a management approach that covers not only marketing channels but also all marketing activities. The increasing importance of long term cooperative relationship lead researchers and market professional to deal with antecedents and outcomes of the relationships in marketing channels. Trust has been examined as a key factor to achieve long term relationships between a supplier and its marketing channels. With this study antecedents of buyer’s trust in Turkish valve market are explained. Communication, supplier’s reputation and supplier’s financial situation are key factors that affect buyer’s trust in the market.
Keywords: Dağıtım Kanalları; Pazarlama; Pazarlama_Güven; Üretim Yönetimi